Irracionalidade e destino no pensamento de Max Weber - Campos, Daniel Vasconcelos (Universidade Federal de São Carlos, 2013)
This dissertation aims at Max Weber´s vision of irrationality. Referring to this, one can stress some points of Weber´s relationship to philosophy. It is particularly highlighted here his opposition to a tradition of thought in which reality is subjected to a practical rationalism. Then, beside questions about the methodology of human sciences, they are also some decisive practical problems to be considered. A quest for the ethical meaning of the world is in the centre of the scene. The concept of irrationality is dealt with on the basis of two specific interests. First, epistemology: irrationality is represented as the split between concept and reality. Second, ethics: it is represented as a split between intention and consequences of action.
Keywords: Irracionalismo (Filosofia); Weber, Max, 1864-1920; Ciências humanas; CIENCIAS HUMANAS::FILOSOFIA